2016
DOI: 10.1371/journal.pone.0147712
|View full text |Cite
|
Sign up to set email alerts
|

Development and Two-Year Follow-Up Evaluation of a Training Workshop for the Large Preventive Positive Psychology Happy Family Kitchen Project in Hong Kong

Abstract: Evidence-based practice and capacity-building approaches are essential for large-scale health promotion interventions. However, there are few models in the literature to guide and evaluate training of social service workers in community settings. This paper presents the development and evaluation of the “train-the-trainer” workshop (TTT) for the first large scale, community-based, family intervention projects, entitled “Happy Family Kitchen Project” (HFK) under the FAMILY project, a Hong Kong Jockey Club Initi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 49 publications
3
17
1
Order By: Relevance
“…The effect size was the greatest in the current study (Cohen’s d ranged from 0.39 to 1.43), compared with those of the HFK TTT (Cohen’s d ranged from 0.37 to 1.22) and the EFWB TTT (Cohen’s d ranged from 0.24 to 1.06) (26, 27). The greater effect size was possibly because the current workshop was the third one we designed in the FAMILY Project to teach social service sector workers to apply positive psychology constructs in family interventions.…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…The effect size was the greatest in the current study (Cohen’s d ranged from 0.39 to 1.43), compared with those of the HFK TTT (Cohen’s d ranged from 0.37 to 1.22) and the EFWB TTT (Cohen’s d ranged from 0.24 to 1.06) (26, 27). The greater effect size was possibly because the current workshop was the third one we designed in the FAMILY Project to teach social service sector workers to apply positive psychology constructs in family interventions.…”
Section: Discussioncontrasting
confidence: 46%
“…The aim of the FAMILY Project is to promote health, happiness, and harmony in Hong Kong (website: ) (25). In the first phase of the project, we conducted two TTTs for the Happy Family Kitchen Project (HFK) and the Enhancing Family Well-being Project (EFWB) to teach social service workers to develop community-based positive psychology family interventions (26, 27) leaving them with some freedom with regard to the specific content of their interventions. The second phase, the Happy Family Kitchen Project-II (HFK-II) aimed to increase public health impact by recruiting a larger sample of underprivileged families from different districts in Hong Kong and to respond to the expressed interest of frontline staff in the design and assessment of programs.…”
Section: Introductionmentioning
confidence: 99%
“…The training workshop was assessed systematically by a four-level model-based evaluation [ 20 ]. The findings showed that the perceived knowledge, self-efficacy and attitude towards the topics covered significantly improved after training, which were similar to the findings of our previous TTT workshops for social workers to implement family well-being programs [ 37 , 38 ]. The effects on knowledge and attitude towards practice were sustained to one year, but not the self-efficacy.…”
Section: Discussionsupporting
confidence: 85%
“…This strategy enables low cost, preventive, and population-wide health promotion interventions ( 5 ). The academic and community collaborative approach ( 6 ) that drives the TTT has been shown to work well outside the West ( 7 ), but there are few studies that include rigorous evaluation of TTTs.…”
Section: Introductionmentioning
confidence: 99%
“…The workshop was delivered to 50 agency staff and was reported to successfully enhance agency staff’s competence and performance in applying positive psychology constructs in their family interventions. Following the workshop, the staff developed and implemented 23 interventions ( 7 ).…”
Section: Introductionmentioning
confidence: 99%